Våld på jobbet: Beskrivningar av våld i arbetslivet 1978–2004 i facklig press (Sociologisk Forskning, 2008)
Violence at work as a social problem: a study of the media coverage on workplace violence in Swedish trade union journals 1978–2004The main purpose of this study was to find out the extent of the unions media coverage on workplace violence and the ways in which the topic was framed. The study shows that the reporting of violence in the workplace described in journals is on a stable level during the period 1978–98. However from the year 2000 and onwards, there is a clear increase in the attention. Four categories of workplace violence were used to identify and recognize different types of violence: intrusive-, consumer-, relationship-and organizational violence. This shows that much of the attention over time has shifted from intrusive violence to organizational violence and consumer violence. What seems to have happened is that workplace violence has become more than just robberies and assaults in the retail business. The stereotypical image of the criminal is challenged by non-traditional criminals like nurses, elderly people and companies. Certain groups, e.g. care workers, come to account for an increasing proportion of attention, both as perpetrators and victims of violence. This study is an important step in understanding the increased reports of workplace violence in Sweden.